2010
DOI: 10.1007/s10886-010-9844-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Biologically Relevant Compounds in Aboveground and Belowground Induced Volatile Blends

Abstract: Plants under attack by aboveground herbivores emit complex blends of volatile organic compounds (VOCs). Specific compounds in these blends are used by parasitic wasps to find their hosts. Belowground induction causes shifts in the composition of aboveground induced VOC blends, which affect the preference of parasitic wasps. To identify which of the many volatiles in the complex VOC blends may explain parasitoid preference poses a challenge to ecologists. Here, we present a case study in which we use a novel bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 46 publications
3
57
0
Order By: Relevance
“…Some of these VOCs may serve to attract pollinators, fruit dispersers and parasitoids of herbivores or as well as to repel herbivores, warn neighbouring plants of imminent herbivore and pathogen attack (Baldwin et al, 2006;Degenhardt and Gershenzon, 2000;Gershenzon and Dudareva, 2007;Hopke et al, 1994;van Dam et al, 2010). Moreover, some BVOCs have been shown to provide protection from environmental stresses such as ozone and high temperatures (Sharkey and Singsaas, 1995;Loreto and Velikova, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these VOCs may serve to attract pollinators, fruit dispersers and parasitoids of herbivores or as well as to repel herbivores, warn neighbouring plants of imminent herbivore and pathogen attack (Baldwin et al, 2006;Degenhardt and Gershenzon, 2000;Gershenzon and Dudareva, 2007;Hopke et al, 1994;van Dam et al, 2010). Moreover, some BVOCs have been shown to provide protection from environmental stresses such as ozone and high temperatures (Sharkey and Singsaas, 1995;Loreto and Velikova, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Guenther et al, 1995Guenther et al, , 2006Grote and Niinemets, 2008) as both enantiomers react at the same rates with ozone and OH. However, for the biosphere (insect and plants) the two enantiomers can be very different and distinct molecules that may elicit opposite responses in pollinators and predators alike (Rostelien et al, 2005;Tooker and Hanks, 2004). Furthermore, variation in the individual enantiomers in ambient air may have the potential to provide clues about variable monoterpene sources within the plant cover through their individual responses to stimuli, and thereby represents a means to better link current empirical models to internal plant processes.…”
Section: Introductionmentioning
confidence: 99%
“…The roots of one of the control plants turned out to be mechanically damaged and the data of this plant were removed from the analysis. Volatiles were desorbed from the traps into the GC-MS (model Trace, ThermoFinnigan, Austin,TX, USA) using an automated thermodesorption unit (model Unity, Markes International Ltd., Llantrisant, UK) as described in [99]. Compounds were identified by their mass spectra using deconvolution software (AMDIS) in combination with NIST 2005 (National Institute of Standards and Technology, USA, http://www.nist.gov) and Wiley 7th edition spectral libraries.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…In plant sciences it is used to study processes inside the plant ( [20]; [180]; [181]) as well as in its interaction with the environment ( [31]; [99]). Within microbiology trace gas analysis can be used to study the metabolism of bacteria ( [126]; [41]), while in medicine it is a promising technique for disease diagnosis/monitoring via breath analysis ( [182]; [183]).…”
Section: Introductionmentioning
confidence: 99%
“…In Lima bean plants, chemical and behavioral analyses have demonstrated that spider mite damage and JA treatment have similar, although not identical, effects on volatile induction . Recently, JA has been used to mimic the induction by herbivores in aboveand belowground multitrophic interaction studies (Qiu et al 2009;van Dam et al 2010). For studies analyzing the differences between root and shoot induction, the additional advantage of using JA is that the induction treatment is qualitatively and quantitatively more comparable for both organs than inductions with different species of real root and shoot herbivores (van Dam and Oomen 2008).…”
Section: Introductionmentioning
confidence: 99%